H.B. 1456 BAN ON OFF DUTY SMOKING BY NEW FIREFIGHTERS (Tufts Archival Research Center, 2007)
Memo regarding a smoking ban in Florida for incoming firefighters. Argues that the ban is unconstitutional as it violates a person's right to privacy under the US and Florida constitutions. Contends that being a non-smoker is not required for employment as a fire fighter. Suggests that the government is trying to avoid bargaining with firefighter representatives by only requiring smoking restrictions from prospective firefighters.